A rare association of emphysematous pyelonephritis with unrecognized diabetes and polycystic kidney - Azzini, A. M. (Medknow Publications, 2009)
Emphysematous pyelonephritis (EPN) is a rare, severe, gas-forming infection for which the treatment of choice is often an immediate nephrectomy, although many reports exist of conservative treatment of cases with antibiotic therapy and percutaneous drainage of abscesses. It usually occurs in diabetic patients and less frequently in subjects with an obstruction of the corresponding renoureteral unit; other predisposing factors are not common. We report here the case of a 51 year-old woman with a rare association of unrecognized diabetes and bilateral polycystic kidney disease who developed monolateral EPN. She had an emergency right nephrectomy and was admitted to Intensive Care Unit (ICU) for septic shock after surgery, requiring intensive resuscitation. The patient was managed with Coupled Plasma Filtration Adsorption (CPFA). Her clinical conditions rapidly improved and the hemofiltration was soon suspended. Urine and blood cultures were positive for the same Escherichia coli, which was susceptible to all tested antibiotics. The patient was transferred to the Nephrology Division and was discharged from the hospital without further dialysis after 34 days. This case report is somewhat unique because of the unusual association between undetected diabetes and polycystic kidney as predisposing factors of a severe infection of the urinary tract.